(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: Hypospadias is a common congenital anomaly affecting the penis, two-stage repair becoming more interesting in era of tubularized incised urethral plate (TIP). Functional outcome of hypospadias repair either single or two stage is as important as cosmetic outcome. In contemporary series , structured scoring systems (Hypospadias Objective Scoring Evaluation-HOSE and Pediatric Penile Perception Scoring -PPPS), evaluation of photographs and uroflowmetry, were used to assess results of hypospadias repair. Objectives: We have assessed outcomes of two-stage hypospadias repair using Hypospadias Objective Scoring Evaluation(HOSE) and uroflowmetry. Material and Methods: Over a period of eight years, from January 1997 to December 2004, One hundred and twenty six hypospadias patients were treated, ninety of them had two-stage repair and36 single-stage repairs. The HOSE questionnaire and uroflowmetry were obtained to evaluate the long term outcome of two stage hypospadias repair. Results: The age at time of assessment ranged from 8 to 23 year-old, with mean follow up of 39.78months. Thrifty five patients had proximal hypospadias and 20 had distal varieties of hypospadias. Operations performed were 37 Bracka?s and 18 Byar?s procedures. Of the 55 patients had complete two stage hypospadias repair and agree to participate in the study , Nineteen patients had acceptable HOSE and 36 had non-acceptable score. Uroflow rates of 43 subjects were below the fifth centile in three patients ,equivocal (between 5th and 25th centile ) in four patients and above 25th centile in 36 subjects. Conclusion: Two stage repair is a suitable technique for all types of hypospadias with versatile outcomes. HOSE and uroflowmetry are simple, easy, non invasive and non expensive tools to assess long term outcomes objectively. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 133-139 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14940